Intercultural competences in teacher training: A polyphonic response to cultural diversity - Lucy, Marie; Gouaïch, Karima (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2024)
This article presents ethnosociological research in educational sciences analyzed from an interdisciplinary and collaborative perspective. The didactics of diversity is discussed with observations and analyses of teaching interculturality in a plural context. Based on observations and analyses, this study questions the notion of intercultural competencies and proposes avenues for teacher training. These aim to support teachers and trainers in the implementation of participatory and innovative pedagogies. The objective is to accompany teachers on current issues in education and on the management of difficult situations in schools. Cultural diversity is both a scientific and ethical issue for higher education and research.